Anti-plane deformation in Green-Naghdi (Type III) thermoelastic medium - Ailawalia, Praveen; Falicki, Jarosław; Salhotra, Sandeep (Zielona Góra: Uniwersytet Zielonogórski)
Anti-plane problems in elastic, viscoelastic, functionally graded material, and thermoelastic medium have been discussed by researchers in the past. The anti-plane problem in the context of Green-Naghdi (Type III) thermoelasticity has been unexplored.
Keywords: cracks; Green-Naghdi; anti-plane; shear stress; temperature distribution